Evaluation Of Medical Information Release Procedures in Ensuring the Legal Aspects of Medical Record Confidentiality at Wangaya General Hospital, Denpasar City - Pascal Reynaldi Abdi Pratama; Ika Setya Purwanti; Putu Ayu Sri Murcittowati (International Journal of Health Engineering and Technology, 2025)
This study aims to evaluate the procedures for releasing medical information at Wangaya Regional General Hospital (RSUD Wangaya) Denpasar City in ensuring the legal aspects of medical record confidentiality. Medical records contain personal and medical data of patients that are confidential, and their release must comply with applicable laws and regulations. This is a qualitative descriptive study using in-depth interviews, observations, and documentation involving five informants, including staff responsible for insurance, reporting, and public relations. The findings indicate that the hospital has a defined flow and mechanism for the release of medical information as outlined in the Standard Operating Procedure (SOP), although challenges remain in terms of completeness of administrative documents. All informants understood the importance of maintaining patient data confidentiality, and the implementation of procedures adheres to relevant regulations such as Law No. 17 of 2023 on Health, Law No. 27 of 2022 on Personal Data Protection, and Ministry of Health Regulation No. 24 of 2022 on Medical Records. It is concluded that the release of medical information at RSUD Wangaya has been carried out in accordance with legal requirements; however, further efforts are needed to strengthen routine socialization to patients and staff, and to periodically evaluate the SOP to ensure the continued protection of patient privacy and data security.